2011
DOI: 10.1002/jobm.201100055
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for sulfur in cell density‐independent induction of luminescence in Vibrio fischeri under nutrient‐starved conditions

Abstract: Despite the universal requirement for sulfur in living organisms, it is not known whether the luminescence of Vibrio fischeri is sulfur-dependent and how sulfur affects the intensity of its luminescence. In this study, we investigated the requirement for sulfur in V. fischeri luminescence under nutrient-starved conditions. Full induction of V. fischeri luminescence required MgSO(4); in artificial seawater cultures that lacked sufficient MgSO(4), its luminescence was not fully induced. This induction of lumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Some studies have shown that cell density‐independent luminescence can be regulated by various factors, such as heat shock proteins , UV irradiation , osmolarity , and redox state . In addition, we recently demonstrated the induction of cell density‐independent luminescence in V. fischeri by the addition of sulfur compounds , which was enhanced by the addition of potassium, bicarbonate, and magnesium . Similarly, in the present study, cell density‐independent luminescence of P. luminescens was induced by the addition of potassium, bicarbonate, and magnesium (Figs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Some studies have shown that cell density‐independent luminescence can be regulated by various factors, such as heat shock proteins , UV irradiation , osmolarity , and redox state . In addition, we recently demonstrated the induction of cell density‐independent luminescence in V. fischeri by the addition of sulfur compounds , which was enhanced by the addition of potassium, bicarbonate, and magnesium . Similarly, in the present study, cell density‐independent luminescence of P. luminescens was induced by the addition of potassium, bicarbonate, and magnesium (Figs.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to these autoinducer‐mediated regulatory mechanisms, we recently demonstrated that the regulation of V. fischeri luminescence in artificial seawater containing NaCl, KCl, MgCl 2 , CaCl 2 , NaHCO 3 , and MgSO 4 was independent of cell density . Moreover, we showed that induction of this type of luminescence required the addition of sulfur‐containing compounds, including sulfate and L‐cysteine , which was enhanced by the addition of potassium, bicarbonate, and magnesium . However, it remains unclear whether the ion composition of the culture medium affects the induction of luminescence in non‐marine luminescent P. luminescens bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…V. fischeri (ATCC 49387) was obtained from the American Type Culture Collection and grown in 100 ml of nutrient broth (NB) (Becton, Dickinson) supplemented with 3% NaCl in 300 ml flasks, which were agitated on a shaker at 70 rpm at 22 °C. V. fischeri was also cultured at 22 °C in artificial seawater (ASW) [16,17], which was composed of 28.1 g/l of NaCl, 0.77 g/l of KCl, 1.21 g/l of CaCl 2 , 4.8 g/l of MgCl 2 ⋅ 6 H 2 O, 0.11 g/l of NaHCO 3 , and 3.5 g/l of MgSO 4 ⋅ 7 H 2 O. Bacterial proliferation was monitored by measuring the increase in optical density of the culture suspension at 600 nm (OD 600 ).…”
Section: Methodsmentioning
confidence: 99%
“…At a low cell density, V. fischeri produces very little luciferase and luminescence, whereas at a higher cell density, these levels are increased. This cell density-dependent induction of luciferase synthesis and resultant luminescence is controlled by diffusible luminescence inducing factors called autoinducers, 17]. In particular, this luminescence type was induced both by inorganic sulfur sources, such as sulfate, sulfite, and thiosulfate, and by organic sulfur sources, including L-cysteine and L-cystine, but not by the addition of autoinducers, such as 3-oxo-C6-HSL or C8-HSL [17].…”
Section: Introduction *mentioning
confidence: 99%
“…In contrast to cell density‐dependent luminescence, we recently discovered cell density‐independent luminescence in V. fischeri induced under nutrient‐starved conditions . Moreover, we demonstrated the induction of this type of luminescence by the addition of sulfur‐containing compounds , which was enhanced by the addition of potassium, bicarbonate, and magnesium . This type of luminescence was induced by both inorganic sulfur sources, e.g., sulfate, sulfite, and thiosulfate, and by organic sulfur sources, including L‐cysteine and L‐cystine .…”
Section: Introductionmentioning
confidence: 71%